Surviving post-natal depression : at home, no one hears you scream - Aiken, Cara, 1964- (Jessica Kingsley Publishers, 2000)
Annotation Research indicates that at least one in ten new mothers experience post-natal depression, yet there is little help available to sufferers. Cara Aiken's book will help them, and the professionals who work with them, to understand this illness. The book tells the stories of ten women from very different backgrounds -- including the author -- who have suffered from post-natal depression. Their stories, told honestly and informally, will be a source of strength and hope for sufferers. The book will also raise awareness of the illness and the destructive effect it can have on individuals and families. It offers positive suggestions and practical advice, based on personal and professional experience. It is a fresh, honest and positive book and an invaluable resource for new mothers, their families and therapists.